THE EFFECTIVENESS OF USING GOOGLE SITES IN TEACHING WRITING FOR SENIOR HIGH SCHOOL AT SMAN 21 GOWA - Suharti, Suharti; Sangkala, Ismail; Hijrah, Hijrah (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This research aims to find out the effectiveness of using Google Sites in teaching writing for senior high school at SMAN 21 Gowa. This research applied a true-experimental method using quantitative approach with a pre-test post-test control group design. There were 40 students of SMAN 21 Gowa involved in this research. The test was a writing test which consisted pre-test and post-test. The findings of this research shows that the use of Google Sites is effective in teaching writing. This is evidenced by the mean pre-test and post-test scores between the experimental group before and after treatment (68.00 became 91.20) and in the control group before and after treatment (67.60 became 85.80) with an increase in the percentage of the experimental group (34%) and control group (26%). It means there is a significant difference before and after using Google Sites in teaching writing. Based on the findings, it concludes that the use of Google Sites is effective in teaching writing for senior high school at SMAN 21 Gowa.